2007
DOI: 10.1097/qad.0b013e32802e6bfa
|View full text |Cite
|
Sign up to set email alerts
|

Treatment interruptions predict resistance in HIV-positive individuals purchasing fixed-dose combination antiretroviral therapy in Kampala, Uganda

Abstract: HIV-positive individuals purchasing generic FDC antiretroviral therapy have high rates of adherence and viral suppression, low rates of antiretroviral resistance, and robust CD4 cell responses. Adherence is an important predictor of survival with full viral suppression. Treatment interruptions are an important predictor of drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
227
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(247 citation statements)
references
References 29 publications
14
227
2
2
Order By: Relevance
“…Both points have been shown to be a significant cause of drug resistance and ARV failure in Uganda. 27 Third, this patients were adequately counselled for improving adherence by counsellors in this ART centre. Counselling is an important factor for improving adherence to antiretroviral therapy in HIV positive patients.…”
Section: Resultsmentioning
confidence: 99%
“…Both points have been shown to be a significant cause of drug resistance and ARV failure in Uganda. 27 Third, this patients were adequately counselled for improving adherence by counsellors in this ART centre. Counselling is an important factor for improving adherence to antiretroviral therapy in HIV positive patients.…”
Section: Resultsmentioning
confidence: 99%
“…in Malawi, where the fertility rate is 5.7 children per woman 56 -stopping and starting ART may be operationally difficult, increase the hazard of death or progression to AIDS, 57 increase the risk of HIV transmission and select for antiretroviral resistance mutations. 58 Indeed, in one study vertical HIV transmission was observed in 0.7% of the women who initiated ART before becoming pregnant and in 5.7% of the women who started ART during pregnancy. 44 Given the health and prevention benefits of lifelong ART in pregnant women, some have argued that programmes should initiate ART immediately after a woman tests positive.…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of adherence to highly active antiretroviral therapy (HAART) remains a key challenge to successful management of patients with HIV/AIDS. It is estimated that adherence rates lower than 95% are associated with development of viral resistance to antiretroviral medications (Nachega, Hislop, Dowdy, Chaisson, Regensberg & Maartens, 2007;Oyugi, Byakika-Tusiime, Ragland, Laeyendecker, Mugerwa, Kityo et al, 2007;Wahl & Nowak, 2000). Adherence has been defined as 'the extent to which a person's behaviour (in terms of taking medications, following diets, or executing lifestyle changes) coincides with medical advice' (Haynes, 1979).…”
Section: Introductionmentioning
confidence: 99%